Beliefs and Practices: Relationship in Using ICTs for Self-initiated Professional Development - M.G. Tessema; G.G. Belihu (Moscow State University of Psychology and Education, 2023)
The purpose of this study was to investigate the relationship between English as Foreign Language (EFL) teachers' beliefs and practices using ICTs for self-initiated professional development (SIPD). The study was carried out in Ethiopia, where teachers are encouraged to engage in self-initiated professional development (SIPD). Similarly, English teachers in Ethiopian higher education institutes are encouraged to engage in self-initiated professional development by assessing and reexamining their teaching beliefs and practices. This can be carried out using information and communication technologies (ICTs). The study participants were EFL teachers from Addis Ababa Science and Technology University. In the study, 35 teachers were selected using total population sampling. Descriptive and correlation methods were employed to analyze the data. Accordingly, although teachers' beliefs were positive, their practice in the use of ICTs for self-initiated professional development was somehow moderate or did not match the level of their beliefs. Therefore, teachers should improve their practice in regard to their strong beliefs about the use of ICTs. All in all, they need to update themselves using the available technologies at their disposal since these technologies provide them with a wide range of ELT's latest developments.